2001
DOI: 10.1107/s160053680101457x
|View full text |Cite
|
Sign up to set email alerts
|

(1S,2S,3R,6S,7R)-3,6-Epoxyhimachalane-2,7-diol

Abstract: Key indicatorsSingle-crystal X-ray study T = 298 K Mean '(C±C) = 0.005 A Ê R factor = 0.037 wR factor = 0.090 Data-to-parameter ratio = 8.2For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Oxidation of β-himachalene 10 was carried out by Benharref et al 99,100 using KMnO 4 . The authors showed that the tetrasubstituted double bond reacted easily with KMnO 4 .…”
Section: Oxidation Of Himachalenes 431 Oxidation With Kmnomentioning
confidence: 99%
“…Oxidation of β-himachalene 10 was carried out by Benharref et al 99,100 using KMnO 4 . The authors showed that the tetrasubstituted double bond reacted easily with KMnO 4 .…”
Section: Oxidation Of Himachalenes 431 Oxidation With Kmnomentioning
confidence: 99%